Home Is Not Here - Wang, Gungwu (Book collections on Project MUSE., 2018)
"One of Asia's most important public intellectuals, Wang Gungwu is best-known for his explorations of Chinese history in the long view, and for his writings on the Chinese overseas. Wang was born in Surabaya, Java, but his parents' orientation was always to China; they had travelled to Southeast Asia to help in the education of the Chinese overseas. Wang grew up in the plural, multiethnic town of Ipoh, Malaya, now Malaysia, was educated at home in the Confucian classics and in English medium schools as a colonial subject. He proceeded from Ipoh to National Central University in Nanjing to study alongside some of the finest of his generation of Chinese undergraduates. The victory of Mao Zedong's Communist Party interrupted his education, and he ends this volume with his return to Malaya. Wise and moving, this is a fascinating reflection on family, identity and belonging, and on the ability of the individual to find a place amidst the historical currents that have shaped Asia and the world."--Provided by publisher.